Difficulties in evaluating the efficacy of antiplatelet therapy in clinical practice - L I Buryachkovskaya; I A Uchitel'; A B Sumarokov; E G Popov; L I Buryachkovskaya; I A Uchitel; A B Sumarokov; E G Popov (Терапевтический архив, 2009)
Aim. To evaluate platelet activity changes in patients with coronary artery disease (CAD) treated with aspirin, clopidogrel and combination of these drugs; to estimate the rate of resistance of CAD patients to antiplatelet treatment. Material and methods. 199 patients with stable CAD were included in the study. Of them, 83 were given aspirin, 46 received clopidogrel, 34 - double antiplatelet therapy (both aspirin and clopidogrel). The trial also studied an additional group of 18 CAD patients on double antiplatelet therapy who had hemorrhages. The control group consisted of 25 healthy volunteers. Platelet aggregation was measured both by a mean size of aggregates (MSA) and light transmission (LTM, Born method) using BIOLA platelet aggregation analyzer. A platelet shape, leukocyte-platelet aggregates (LPA) and erythrocyte-platelet aggregates (EPA) in the whole blood were studied using scanning electron microscopy. The levels of IL-6 and sVCAM were also measured. Results. It was found that 59.8% patients with CAD had high platelet reactivity revealed in 94.9% of cases by measuring spontaneous and induced by 0.1 mcM ADP platelet aggregation. LTM revealed increased platelet reactivity only in 10.7% patients. Resistance to aspirin correlated with the presence of LTA (r = 0.629, p = 0.0001) and the number of large "reticulated" platelets (r = 0.334, p = 0.001). Low platelet reactivity was associated with the presence of circulating EPA (r = -0.362, p = 0.008). Administration of clopidogrel did not decrease platelet reactivity to normal levels in 34.7% patients which correlated with the presence of LPA and EPA. In 83.3% patients with hemorrhages platelet aggregation, induced by 5.0 mcM, ADP was dramatically decreased. Conclusion. Resistance to antiplatelet therapy is related to platelet heterogeneity, the presence of inflammation and state of erythrocytes. LT is capable to reveal only a part of patients resistant to antiplatelet drugs. To fully identify these patients, it is necessary to register spontaneous platelet aggregation and aggregation induced by low doses of ADP. Redundant inhibition of platelet reactivity could be the cause of hemorrhagic events.